Estudo da composição química dos óleos essenciais e as atividades antioxidante, antimicrobiana e antiprotozoária do óleo essencial e de extratos etanólicos de folhas de Qualea grandiflora e Qualea multiflora Mart. - Rocha, Rodrigo Ribeiro (2014)
The purpose of this study was to assess the chemical composition of the essential oils obtained from leaves of Qualea grandiflora Mart. and Qualea multiflora Mart.. Was assessed the total reducing power by means of analysis of differential pulse voltammetry, antimicrobial activity toward aerobic and anaerobic oral bacteria, as well as of antileishmanial and cytotoxicity activities (Vero cells). Was also assessed the antioxidant activity of ethanolic extracts obtained from leaves by means of the sequestering of radical DPPH and β-carotene/linoleic acid based methods, and was determined the content of total phenols, was assessed the total reducing power by means of analysis of differential pulse voltammetry, antimicrobial activity toward aerobic and anaerobic oral bacteria, as well as of antileishmanial and cytotoxicity activities (Vero cells). Regarding the chemical constituents of essential oils, was found the presence of the following classes of compounds for Qualea grandiflora: oxygenated sesquiterpenes (36.6.%), oxygenated monoterpenes (12.2%), and aldehydes and carboxylic acids, each found in around 4.9%. For Qualea multiflora, were found the oxygenated monoterpenes (29.3%), alcohols (19.5%), aldehydes (12.2%) and ketones (7.3%). There was no activity in the differential pulse voltammetry experiment of samples of essential oils obtained from leaves of both species. Regarding the antioxidant activity, and the experiment of determining the content of total phenols, the ethanolic extracts obtained from leaves of Qualea grandiflora showed better results of CE50 for antioxidant experiments of DPPH and β-carotene than the ethanolic extract obtained from leaves of Qualea multiflora. The differential pulse voltammetry was according to spectrophotometric results, and to differential pulse voltammetry. There was no antimicrobial activity of ethanolic extracts and essential oils obtained from leaves of both species toward oral bacteria. Was found antileishmanial activity for Qualea grandiflora (IC50 88 ± 8 μgmL-1) and Qualea multiflora (IC50 69 ± 4 μg.mL-1) toward Leishmania amazonensis, and low cytotoxicity of Vero cells, with the presence of essential oils obtained from leaves. There was not found the same activity from ethanolic extracts obtained from leaves. The performing of this work showed a part of scientific knowledge related to the studied species, and the possible validation of their medicinal use. In the future, this study could help in the experimentation, testing, manufacturing, commercialization and use of medicines from products obtained from medicinal plants of the Cerrado, since nowadays, many of them are used in the popular medicine. In the experiments where there was no activity, further testing should be performed seeking to obtain activity.